VARIASI SUHU MUKA LAUT BULANAN BERDASARKAN KANDUNGAN KIMIA KORAL - Cahyarini, Sri Yudawati; Pfeiffer, Miriam; Prayudi, Dudi (Teknologi Indonesia, 2009)
Information on environmental changes which is available today is limited to only dozen years back. In order to make an assesment on environmental changes, information on longer time is required. Corals can provide environmental data till thousand years back. To have some information, it is required to analyze geochemical proxy. By analyzing geochemical elements such as Sr/Ca, ?18O, sea surface temperature and salinity can be reconstructed. Further, by analyzing and interpreting time series data of coral geochemical proxy can be used to understand intensity, process, and mechanism of the environmental damage. In this study, reconstruction of sea surface temperature using Sr/Ca and ?18O coral from Timor is used as a case. The result shows that Sr/Ca is influenced by sea surface temperature.